Assessing the Selection of Digital Learning Materials: A Facet of Pre-Service Teachers’ Digital Competence - Peter Gonscherowski; Edith Lindenbauer; Kai Kaspar; Benjamin Rott (Applied Sciences)
Given the increasing digitalization of education and the variety of available digital learning materials (dLMs) of differing quality, (pre-service) teachers must develop the ability to select appropriate dLMs. Objective, reliable, and valid assessment instruments are necessary to evaluate the effectiveness of that development. This study conceptualized and designed an economical four-item instrument for assessing “selecting dLMs” based on accepted frameworks and competence models. The scientific quality of the instrument was evaluated in Study 1 (n = 164) with four dLMs and empirically investigated in a subsequent Study 2 (n = 395) with pre-service mathematics teachers from two universities. The empirical results indicate that the instrument could objectively and reliably gauge different levels of “selecting dLMs”. Furthermore, the results are consistent with the widely accepted notion that the competence of “selecting dLMs” depends on (content) knowledge; however, that relation was not strong. In addition, the results for objectively assessing “selecting dLMs” paralleled the results of self-assessed TPACK in terms of the academic progression of participants. The proposed approach allows for variations and integration of diverse dLMs, and it has the potential to be adapted in other subject areas and contexts.